2017
DOI: 10.3390/ijerph14050533
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Healthy Lifestyle and Well-Being in Adolescents through Outdoor Physical Activity

Abstract: Health-enhancing physical activities (PA) performed outdoors could markedly contribute to the adoption of a healthy lifestyle in adolescence. The differences between PA preferences and actual opportunities for these PA are an issue that has received frequent attention. To date, the extent to which these differences are reflected in adolescents meeting PA recommendations and their well-being has not been explored. In total, 10,086 respondents took part in an on-line research project regarding PA preferences. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 56 publications
6
50
0
3
Order By: Relevance
“…Its use for adolescents aged 15-17 significantly correlated for time spent in active travel, for moderate and vigorous activities as well as for total physical activity [39,40]. Both versions were subject to the required translation procedure according to the 'EORTC (European Organisation for Research and Treatment of Cancer) Quality of Life Group' [41] and empirically verified in international comparative studies [26,42]. Among the several types of PA measured, the IPAQ-LF includes transport PA (cycling and walking activities for at least 10 minutes at a time to go from place to place).…”
Section: Subjective Estimation Of Weekly Pamentioning
confidence: 99%
“…Its use for adolescents aged 15-17 significantly correlated for time spent in active travel, for moderate and vigorous activities as well as for total physical activity [39,40]. Both versions were subject to the required translation procedure according to the 'EORTC (European Organisation for Research and Treatment of Cancer) Quality of Life Group' [41] and empirically verified in international comparative studies [26,42]. Among the several types of PA measured, the IPAQ-LF includes transport PA (cycling and walking activities for at least 10 minutes at a time to go from place to place).…”
Section: Subjective Estimation Of Weekly Pamentioning
confidence: 99%
“…In this study, we present results concerning moderate-to-vigorous PA (MVPA) intensity (60-100% HRmax, ≥3 METs). e accelerometer data were processed consistent with previously published methods [38][39][40][41].…”
Section: Assessment Of Physical Activitymentioning
confidence: 99%
“…Given recent trends in adolescents' PA, one can infer that the most widespread recommendations of 10,000 steps/day [47,48], 10,000-11,700 steps/day [34], 12,000 steps/day [49,50,51], the 11,000 steps/day for both boys and girls promoted by our team [41,52,53], or 13,000-16,000 steps/day focused on weight-reduction behaviours [54], are not accepted well by adolescents with lower levels of PA. In Canada, Colley et al [50] suggested revising the recommendation from 13,500 to 12,000 steps/day among 6-19-years-old children and adolescents, which they found more appropriate benchmark for assessing the guideline of 60 min of daily moderate-to-vigorous PA.…”
Section: Discussionmentioning
confidence: 99%